2015
DOI: 10.1161/circulationaha.115.015484
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization Therapies in Acute Ischemic Stroke Patients

Abstract: Background-We explored the safety of intravenous thrombolysis (IVT) or intra-arterial treatment (IAT) in patients withischemic stroke on non-vitamin K antagonist oral anticoagulants (NOACs, last intake <48 hours) in comparison with patients (1) taking vitamin K antagonists (VKAs) or (2) without previous anticoagulation (no-OAC). Methods and Results-This is a multicenter cohort pilot study. Primary outcome measures were (1) in no-OAC patients. sICH ECASS-II and sICH NINDS occurred in 2.6%/3.9% NOAC patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 49 publications
3
36
0
1
Order By: Relevance
“…Among the case reports, ICH and poor outcome were rarely reported when recombinant tissue-type plasminogen activator was administered minutes to 24 hours after the last anticoagulant dose. 74,75 The cohort study 76 comprised 78 NOAC-treated patients undergoing intravenous thrombolysis or intra-arterial therapy a median of 13 hours after the last NOAC dose compared with 441 warfarin-treated patients and 8938 on no anticoagulants. After propensity score matching, there was no significant difference in rate of any ICH, symptomatic ICH, or death among the groups.…”
Section: Management Of Patients On Noacs Who Are At Risk For Bleedingmentioning
confidence: 99%
“…Among the case reports, ICH and poor outcome were rarely reported when recombinant tissue-type plasminogen activator was administered minutes to 24 hours after the last anticoagulant dose. 74,75 The cohort study 76 comprised 78 NOAC-treated patients undergoing intravenous thrombolysis or intra-arterial therapy a median of 13 hours after the last NOAC dose compared with 441 warfarin-treated patients and 8938 on no anticoagulants. After propensity score matching, there was no significant difference in rate of any ICH, symptomatic ICH, or death among the groups.…”
Section: Management Of Patients On Noacs Who Are At Risk For Bleedingmentioning
confidence: 99%
“…11 Importantly, although guidance for the interpretation of coagulation test result allowing safe thrombolysis in patients on NOAC treatment have been proposed, 12,13 data supporting their validity is limited. 11,14 The impact of time-consuming NOAC-specific coagulation testing in acute stroke management is currently unclear, and the actual use of these tests in clinical practice is unknown.…”
mentioning
confidence: 99%
“…Although few studies compare the severity and functional repercussion of stroke in patients receiving VKAs and DOACs, it does seem clear that appropriate anticoagulant therapy is associated with a greater probability of moderate or severe stroke and in-hospital mortality [15][16][17]. In our study, we observed that patients receiving treatment with DOACs were statistically significantly more likely to experience transient stroke and partial anterior circulation infarct than patients receiving VKAs, which are usually indicative of less severe infarcts and better functional outcomes.…”
Section: Discussionmentioning
confidence: 49%